Local existence for a general model of size-dependent population dynamics. (1997) - Kato, Nobuyuki; Torikata, Hiroyuki
Abstract : We shall investigate a size structured population dynamics with aging and birth functions having general forms. The growth rate we deal with depends not only on the size but also on time. We show the existence of a local solution and continuous dependence on the initial data, which shows the uniqueness of the solution as well.